The university teacher and the new challenges of teaching in Peru: motivating to learn - Toribio López, Alexander (2021)
In university classrooms, the level of student attention and motivation greatly facilitates the work of the professor. However, these two elements are not always present to the extent required for effective learning. In this paper, we begin by exploring student behavior, placing an emphasis on the attention and motivation of the new generations of students, and their relationship with the access to information and new technologies. In addition, we review the vision of the main international organizations on educational quality, and the importance of professors achieving that their students obtain effective learning, anecessary condition for both a successful insertion into the competitive labor market, and a positive contribution to society. We also carry out an historical review of the role university professors have u and their responsibility as agents of change; transmitters of knowledge; and skill developers. We conclude that professors could motivate their students to learn by incorporating constructive humor into their teaching, which would also make them improve their attitude; install a climate favorable to effective learning in the classroom; communicate more closely with their students; and with it, get a better chance to face the new challenges of teaching at higher education institutions in Peru.